Promoting epithelial regeneration in chemically induced acute lung injury through Sox9-positive alveolar type 2 epithelial cells - Chao Cao; Obulkasim Memete; Yu Dun; Lin Zhang; Fuli Liu; Daikun He; Jian Zhou; Yiru Shao; Jie Shen (Stem Cell Research & Therapy)
Abstract Background Chemical-induced acute lung injury is characterized by impaired epithelial regenerative capacity, leading to acute pulmonary edema. Numerous studies have investigated the therapeutic potential of endogenous stem cells with particular emphasis on alveolar type 2 epithelial (AEC2) cells owing to their involvement in lung cell renewal. Sox9, a transcription factor known for its role in maintaining stem cell properties and guiding cell differentiation, marks a subset of AEC2 cells believed to contribute to epithelial repair. However, the role of Sox9+AEC2 cells in the distal lung alveolar cells and the potential roles in chemically induced acute lung injury have never been explored. Methods In this study, we generated Sox9 flox/flox ;Sftpc Cre−ERT2 mice and examined the effects of Sox9+AEC2 cells on the pathophysiology of epithelial damage during chemical-induced acute lung injury. Subsequently, Sox9-Cre ERT2 Ai9 mice were used for lineage tracing to elucidate the repair mechanisms. Results Our findings revealed that Sox9+AEC2 cells endowed with stem cell properties induced cell proliferation during lung injury, predominantly in the damaged alveolar region. This process is accompanied by the regulation of inflammatory responses and orderly differentiation, thereby promoting epithelial regeneration. Conclusion These results provide compelling in vivo genetic evidence supporting the characterization of Sox9+AEC2 cells as bona fide lung epithelial stem cells, demonstrating their multipotency and self-renewal capabilities during lung repair and regeneration. The identification of Sox9+AEC2 cells as crucial contributors to the promotion of epithelial repair underscores their potential as therapeutic targets in chemical-induced acute lung injury.